Utilidad de la relación proteinuria:creatininuria en muestra aislada en el diagnóstico diferencial de preeclampsia - Valdés R., Enrique; Castro L., Magdalena; Castro C., Daniela; Sepúlveda-Martínez., Álvaro (Revista Hospital Clínico Universidad de Chile, 2012)
Preeclampsia is an important cause of perinatal morbidity and mortality locally and globally. Diagnosis requires a 24 hours urine collection to determine the protein level. Current investigations had been focused on extrapolate the protein: creatinine ratio to pregnant patients, as a fast method to diagnose preeclampsia. This literature review establish that apparently there is a relationship between protein: creatinine ratio and 24 hours protein collection, but more research is still needed to establish an international consensus with respect to cut off value or measure units.